1999
DOI: 10.1093/oxfordjournals.jbchem.a022544
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Molecular Cloning, and Genomic Organization of Human Brain Long-Chain Acyl-CoA Hydrolase

Abstract: An acyl-CoA hydrolase, referred to as hBACH, was purified from human brain cytosol. The enzyme had a molecular mass of 100 kDa and 43-kDa subunits, and was highly active with long-chain acyl-CoAs, e.g. a maximal velocity of 295 micromol/min/mg and K(m) of 6.4 microM for palmitoyl-CoA. Acyl-CoAs with carbon chain lengths of C(8-18) were also good substrates. In human brain cytosol, 85% of palmitoyl-CoA hydrolase activity was titrated by an anti-BACH antibody, which accounted for over 75% of the enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…long-chain acyl-CoA substrates with fatty acid chains of [8][9][10][11][12][13][14][15][16] carbon atoms (C 8 -C 16 ) (7,13). Acot7 contains a pair of fused thioesterase domains that share Ϸ30% sequence identity, with each thioesterase domain predicted to have the hotdog fold structure with an ␣-helix sausage wrapped by a ␤-sheet bun (14)(15)(16).…”
mentioning
confidence: 99%
“…long-chain acyl-CoA substrates with fatty acid chains of [8][9][10][11][12][13][14][15][16] carbon atoms (C 8 -C 16 ) (7,13). Acot7 contains a pair of fused thioesterase domains that share Ϸ30% sequence identity, with each thioesterase domain predicted to have the hotdog fold structure with an ␣-helix sausage wrapped by a ␤-sheet bun (14)(15)(16).…”
mentioning
confidence: 99%
“…It has been shown that Acot7 isoenzymes account for approximately 80-90% of the acyl-CoA thioesterase activity in brain (13,16). However, mRNA is mainly detected in testis, with lower levels in brain and even lower levels in the other tissues, although protein is highest in brain, followed by testis, lung and lower in the other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the major isoform of the Acot7 gene expressed in brain and testis is the cytosolic Acot7_v1 (previously known as CTE-II or BACHa) (10,13). In order to characterize the mouse gene encoding the Acot7_v1, searches were carried out in mouse EST databases for different 5' ends of Acot7.…”
Section: Identification and Mapping Of Alternative First Exons In Thementioning
confidence: 99%
See 2 more Smart Citations